(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This research paper aims to explore the effectiveness of using web technology in teaching vocabulary to learners of higher education. With the increasing use of technology in various aspects of education, it is essential to investigate its potential in enhancing vocabulary acquisition. This study will examine the impact of web-based tools, applications, and platforms on vocabulary learning, as well as the benefits and challenges associated with their implementation. Additionally, it will provide practical recommendations for educators on how to effectively integrate web technology into vocabulary instruction to promote meaningful and engaging learning experiences.